Posted by
**Hannah** on
.

For f(x) = 2x-3 and g(x)= 2x^2 find,

a) (f + g)(x) = My answer is

2x^2 + 2x - 3. Is this correct?

b) (f - g)(x) How would you do this?

c) (f X g)(2) I do not know what to do since the 2 is there.

Determine whether the graph of the following equation is symmetric with respect to the x-axis, the y-axis, and the origin.

y^2 - x - 49 = 0

For x axis -y^2 - x - 9 = 0 is not the same as the first equation so it is not symmetrical to the x-axis. Correct?

For the y-axis y^2 + x - 49 = 0 is not the same as the first equation so it is not symmetrical to the y-axis. Correct?

For the origin -y^2 + x - 49 = 0 is not the same as the first equation so itis not symmetrical to the origin either. Am I correct?